Ophthalmic findings of congenital insensitivity to pain with anhidrosis with a novel neurotrophic tyrosine kinase receptor type 1 gene mutation: A case report - Zhu, Rong; Zhu, Yuxiang; Xu, Mingpeng; Gu, Zhensheng (Frontiers in Medicine, 2022)
We report a case of congenital insensitivity to pain with anhidrosis (CIPA) with a novel neurotrophic tyrosine kinase receptor type 1(NTRK1) gene mutation. The patient suffered from recurrent corneal ulcer. A slit-lamp examination revealed ciliary hyperemia, bulbar conjunctival edema, epithelial defect, and ulcer lesion in the inferior part of the cornea, local corneal stromal edema accompanied by new vascular growth in his affected eye. In addition, the corneal sensitivity and nerve fiber density decreased significantly in both eyes. Tear film break-up time and Schirmer’s I test were below lower limit. Moreover, the patient exhibited typical systemic features, including no normal response to pain stimuli, anhidrosis and self-injurious behavior. Gene sequencing revealed a compound-heterozygous mutations in NTRK1 gene: a missense mutation inherited from his mother (c.1750G > A, P.E584K) and a new splicing mutation inherited from his father (c.2187 +5G>C). After 8 weeks of medication, the corneal ulcer basically healed. This study expands the spectrum of NTRK1 gene mutation associated with CIPA and provides a feasible approach for clinicians to treat patients with CIPA-related keratopathy.